The Two Traditions of Meditations in Ancient India - John B. Chethimattam, (Journal of Dharma, 1994)
In this book.i.Johannes highlights the early Buddhist teachings and briefs concerning meditation and its role to liberation. It is to find but what early Buddhist meditation was bv asserting what it: was riot. In a number of cases the Buddhist cannon rejects practices which they accept elsewhere. The altre~native practices hi Buddhism cannot be considered as authentic but as later borrowing from out side. This book, in fact, allows us to, obtain more insight into the alternative, non-Buddhist.' practices especially of the early period.